2022
DOI: 10.1039/d2ra02315f
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride and APTES modified advanced electrochemical biosensor for detection of 17β-estradiol in spiked food samples

Abstract: This work demonstrates a simple and inexpensive electrochemical biosensing pathway for selective and sensitive recognition of 17β-estradiol (E2) in environmental and food samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Biosensors can be used for the detection of female sex hormone named 17β-estradiol, which is known as a natural and bio-identical form of estrogen. A recent report by Bacchu et al , 148 showed that the biosensor, g-C 3 N 4 /APTES/SPE (g-C 3 N 4 = graphitic carbon nitride, APTES = 3-aminopropyltriethoxysilane, SPE = screen-printed electrode) is very effective and can detect estradiol with a wide range of linearity from 1 × 10 −6 to 1 × 10 −18 mol L −1 , LOD of 9.9 × 10 −19 mol L −1 , high selectivity, and stability. Other biosensors, such as aptamer-based label-free biosensors, 149–153 near-infrared (NIR) phosphorescence aptasensor, 154 split aptamer regulated CRISPR/Cas12a (CRISPR = Clustered Regularly Interspaced Short Palindromic Repeats, Cas12a = RNA-guided endonuclease) biosensor, 155,156 Hydrogel optical waveguide spectroscopy a label-free biosensor, 157 highly sensitive laccase-based biosensor, i.e.…”
Section: Nanostructured Wearable Biosensormentioning
confidence: 89%
“…Biosensors can be used for the detection of female sex hormone named 17β-estradiol, which is known as a natural and bio-identical form of estrogen. A recent report by Bacchu et al , 148 showed that the biosensor, g-C 3 N 4 /APTES/SPE (g-C 3 N 4 = graphitic carbon nitride, APTES = 3-aminopropyltriethoxysilane, SPE = screen-printed electrode) is very effective and can detect estradiol with a wide range of linearity from 1 × 10 −6 to 1 × 10 −18 mol L −1 , LOD of 9.9 × 10 −19 mol L −1 , high selectivity, and stability. Other biosensors, such as aptamer-based label-free biosensors, 149–153 near-infrared (NIR) phosphorescence aptasensor, 154 split aptamer regulated CRISPR/Cas12a (CRISPR = Clustered Regularly Interspaced Short Palindromic Repeats, Cas12a = RNA-guided endonuclease) biosensor, 155,156 Hydrogel optical waveguide spectroscopy a label-free biosensor, 157 highly sensitive laccase-based biosensor, i.e.…”
Section: Nanostructured Wearable Biosensormentioning
confidence: 89%
“…Therefore, a hydrogel-based electrochemical biosensor was proposed to detect glucose via electrochemical impedance spectroscopic (EIS) measurements [42]. An electrochemical biosensor based on graphitic carbon nitride (g-C 3 N 4 ) and a conductive polymer 3-aminopropyltriethoxysilane (APTES) was developed to carry out the selective and sensitive determination of hormone 17β-estradiol [43].…”
Section: Electrochemical Biosensors In Food and Food Product Safetymentioning
confidence: 99%
“…27,28 Accordingly, developing efficient and sensitive methods for the monitoring of E2 levels is of great significance. So far, many different techniques have been established for the determination of E2, such as gas chromatography/liquid chromatography–mass spectrometry (GC/LC-MS), 29,30 enzyme-linked immunosorbent assay (ELISA), 31,32 colorimetry, 33–35 fluorescence, 36–39 electrochemistry, 40–46 and surface-enhanced Raman spectroscopy. 47,48 Nevertheless, these methods might suffer from the high cost of devices, the need for high levels of technical skill, low sensitivity, cumbersome operation processes and the need for sample pretreatment.…”
Section: Introductionmentioning
confidence: 99%